A bibliometric and thematic analysis of the reputation-performance relationship within the triple bottom line framework - Francisca Castilla-Polo; María Isabel Sánchez-Hernández (European Research on Management and Business Economics)
This study analyses the academic literature on the relationship between reputation and performance, exploring the different perspectives applied. It addresses a research gap by extending the scope of reputation management from a financial focus to a Triple Bottom Line approach incorporating social and environmental dimensions. A bibliometric analysis of records extracted from the Web of Science database was conducted using VOSviewer, followed by a thematic analysis with ATLAS.ti. Four main research domains were identified: (1) the financial domain, emphasizing financial performance and featuring prominent foundational works; (2) corporate social responsibility and sustainable practices, a well-established area focusing on social performance; (3) the emerging environmental domain; and (4) the strategic vision domain, which addresses microeconomic topics such as knowledge management and competitive advantage. This study summarizes key contributions, identifies future research directions, and establishes a tentative research agenda. Practitioners can use these insights to enhance reputation management processes, yielding financial, sustainability, and strategic benefits.